Trial by fire: The qualitative essence of interns' baptism into medical responsibility - M Yogesh; Anurag Ekka; Rohankumar Gandhi; Naresh Damor (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: The transition from medical student to intern represents a challenging period of professional and personal development. This study aimed to explore junior doctors' experiences navigating this critical passage. MATERIALS AND METHODS: An exploratory qualitative study was conducted on a junior intern doctor working in a tertiary care hospital, in Gujarat. About 40 junior doctors participated in semi-structured interviews reflecting on their internship transition. Data were analyzed using thematic analysis. RESULTS: Perceived deficits in preparedness for clinical work and emotional readiness were a major theme. Interns felt underprepared in skills like clinical reasoning and procedures. The abrupt onset of patient care responsibility provoked anxiety and eroded confidence. Difficulty adapting to workplace culture and hierarchies was another challenge. Long work hours, unfamiliar team dynamics, and new professional relationships were demanding. The intensity of workload and patient care duties provoked overwhelming stress, fatigue, and burnout risk during the junior doctor transition. Peer support and mentoring facilitated adaptation. Enhanced undergraduate training in practical skills and professional competencies was advised to improve preparedness. CONCLUSION: Junior doctors face major challenges to their well-being, confidence, and competence as they transition into clinical practice. Support structures to ease this demanding passage of professional development are needed. Medical schools must strengthen curricula to address preparedness gaps. Improved onboarding and supervised orientation may also benefit new interns. Facilitating an optimal student-to-doctor transition has important implications for physician training, satisfaction, and retention.